Prevalence, Awareness, Treatment, and Control of Hypertension and Its Risk Factors in (Central) Vietnam. (16th May 2018) - Hien, Ho Anh; Tam, Nguyen Minh; Tam, Vo; Derese, Anselme; Devroey, Dirk
Abstract : Introduction . The objective of this study is to describe the prevalence, awareness, treatment, and control of hypertension and its associated risk factors in (Central) Vietnam. Methods . In this cross-sectional study, a multistage sampling was used to select 969 participants from the general population aged from 40 to 69 years. The cardiovascular risk factors were collected throughout the interviews with a standardized questionnaire. Multivariate logistic regression analysis was conducted to test the relationship between the prevalence, awareness, treatment, and control of hypertension and the prevalence of risk factors. Results . The prevalence of hypertension was 44.8%. It was higher in men than in women (51.3% versus 39.7%, p < 0.001). In total 67.3% (74.5% in women, 60.1% in men; p = 0.001) of the participants were aware of their hypertension, 33.2% (37.5% in women, 28.9% in men; p = 0.01) of the participants were treated, and 12.2% (16.7% in women, 7.8% in men; p < 0.001) of the hypertensive participants' hypertension was controlled. Age, gender, place of residence, body mass index, and diabetes were found to be independent risk factors for hypertension. Conclusion . The prevalence of hypertension in Vietnam is high, and the proportion of treated and controlled patients is rather low.